PEMBELAJARAN PKn BERBASIS MULTIKULURALISME PERSPEKTIF PSIKOLOGI SOSIAL ISLAM - Baidi, Baidi (ULUL ALBAB Jurnal Studi Islam, 2014)
This article describes a multicultural learning-based Civics in social psychology perspective of Islam which includes the relation between; Civics with Islamic social psychology, Civics with multiculturalism, Islam and multiculturalism Social Psychology, Civics with multiculturalism and social psychology Islam. The method used is descriptive qualitative to describe the relationship existing facts embaded design case study. The findings indicate that the diversity of the community is a necessity. The diversity can lead to vulnerability to conflict. Some conflicts in various regions realize the importance of maintaining harmony in diversity. To prevent conflicts requires an understanding citizens against multiculturalism in a diverse society. Understanding of multiculturalism can be taught through learning -based Civics Social Psychology perspective of multiculturalism in Islam. It is expected that smart and good citizenship is a manifestation of multiculturalism in the Indonesian context.